Interface-Dominated Topological Transport in Nanograined Bulk Bi2Te3 - Izadi, Sepideh; Han, Jeong Woo; Salloum, Sarah; Wolff, Ulrike; Schnatmann, Lauritz; Asaithambi, Aswin; Matschy, Sebastian; Schloerb, Heike; Reith, Heiko; Perez, Nicolas; Nielsch, Kornelius; Schulz, Stephan; et al. (Small, 2021)
3D topological insulators (TI) host surface carriers with extremely high mobility. However, their transport properties are typically dominated by bulk carriers that outnumber the surface carriers by orders of magnitude. A strategy is herein presented to overcome the problem of bulk carrier domination by using 3D TI nanoparticles, which are compacted by hot pressing to macroscopic nanograined bulk samples. Bi2Te3 nanoparticles well known for their excellent thermoelectric and 3D TI properties serve as the model system. As key enabler for this approach, a specific synthesis is applied that creates nanoparticles with a low level of impurities and surface contamination. The compacted nanograined bulk contains a high number of interfaces and grain boundaries. Here it is shown that these samples exhibit metallic-like electrical transport properties and a distinct weak antilocalization. A downward trend in the electrical resistivity at temperatures below 5 K is attributed to an increase in the coherence length by applying the Hikami–Larkin–Nagaoka model. THz time-domain spectroscopy reveals a dominance of the surface transport at low frequencies with a mobility of above 103 cm2 V−1 s−1 even at room temperature. These findings clearly demonstrate that nanograined bulk Bi2Te3 features surface carrier properties that are of importance for technical applications.
CRIS-Team Scopus Importer:2022-04-14
Keywords: bismuth telluride; nanograined bulk; THz spectroscopy; topological insulators; weak antilocalization